Smart City - A new concept of green and technological city - A survey will explain the differences between two countries with a different vision of these cities - Stefano CARBONI (Smart Cities and Regional Development Journal)
Objectives The search for the meaning of the term of the new cities called "Smart City". Approach the search for articles that explain the meaning of smart cities and offer an explanation of this term. A survey is useful for understanding if the population of a nation knows these new cities, and what they think of them. Results Several authors speak of smart cities and therefore different definitions of these cities can be found. to overcome this, six characteristics have been identified, which have been accepted by all. From the answers of the survey it can be observed that smart cities are known by almost all the population of Italy and Norway.